FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MINAT AKSEPTOR MENGGUNAKAN KONTRASEPSI IUD DI PUSKESMAS MUARA KUANG TAHUN 2024 - Anggraini, Meta; Arif, Ahmad; Anggraini, Arie; Rahmawati, Eka; Dewi, Ratna (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2025)
Population problems have been a problem for many years in both developed and developing countries, including Indonesia. There are 10 countries with the largest population in the world, where the first rank is India with a population of 1.44 billion, second is China with a population of 1.43 billion, followed by the United States with a population of 341.03 million, and Indonesia is ranked fourth with a total of 278.82 million. The prevalence of modern contraceptive use or mCPR has increased, where in 2022 contraceptive use will be 58.7% (WHO, 2022). The aim of this research was to determine the relationship between knowledge, reproductive age and husband's support on acceptors' interest in using IUD contraception at the Muara Kuang Community Health Center. This type of research uses a quantitative analytical survey with a Cross Sectional research design. The population in this study were all mothers who used contraception. The sample in this study used the Slovin formula to obtain a sample of 56 respondents with a sampling technique using incidental sampling. Data were analyzed using the Chi-Square test. Univariate analysis found that there were 8 (14.3%) fewer mothers who were interested in using IUD contraception compared to 48 respondents (85.7%) who did not use IUD contraception. The results of the bivariate analysis showed that there was a significant relationship between maternal knowledge where the value was (P-Value = 0.014), there was a significant relationship between reproductive age where the value was (P-Value = 0.023), and there was a significant relationship between husband's support where (P-Value = 0.035) on acceptor interest in using IUD contraception at the Muara Kuang Health Center. The conclusion is that there is a relationship between knowledge, reproductive age and husband's support on interest in using IUD contraception.